Basic Digital Marketing Training for the Community and Students of Mahkota Tricom Unggul University - Rozy, Ahmad; Jannah, Miftahul; Larasati, Fadya; Azi, Muhammad; Sari, Suci Amalia (Jurnal Pengabdian Pancasila (JPP), 2024)
Basic Digital Marketing Training for the community and students of Mahkota Tricom Unggul University aims to increase understanding and skills in digital marketing. This activity is motivated by the need for digital knowledge which is increasingly important in the technological era. Through situation analysis, several problems were identified, such as lack of knowledge and fierce competition. The solution offered is counseling and training involving experienced resource persons. The expected outcomes include increased community awareness, independence, and quality of life through the utilization of digital marketing. The implementation method includes lectures, discussions, and demonstrations, with the hope that this activity can be sustainable and have a positive impact on the community and students.